Editorial - Anais da III Semana do Aparelho Digestivo de Rondônia - Gastro 2022 - de Brito, Nicolas Pereira; Ramos, Ana Maria Bezerra; Vaiciunas, Spencer; Igi, William Ferreira; Leite, Cleber Queiroz; dos Santos, Brian França; de Aquino, Alana Guimarães; Torres, Ananda Sampaio; Pires, Bárbara Barbosa; Ribera, Beatriz Azevedo; da Silva, Débora Alves; Domingos e Silva, Isabelle Giacomett de Carvalho; et al. (Brazilian Journal of Case Reports, 2022)
Não se aplica.